2021
DOI: 10.1002/jbm.b.34918
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid‐loaded hemostatic nanoclay microsphere frameworks

Abstract: Fast acting topical hemostatic agents play a key role in hemorrhage control.Retarding fibrinolysis is also critical in improving coagulation, thereby expanding chances of survival. The purpose of the present work was to investigate the physical properties, loading capacity and hemostatic efficacy of newly developed nanoclay microsphere frameworks (NMFs) loaded with tranexamic acid (TA), as antifibrinolytic agent. Nanoclay compositions were prepared with increasing levels of TA. Results showed that TA was succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The results of the nitrogen sorption analysis 58 are also presented in this section and summarized in Figure 3. The synthesized MCM‐41 nanoparticles had a specific surface area, pore volume and pore diameter of 1123.335 m 2 g −1 , 1.701 m 3 g −1 , and 2.342 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the nitrogen sorption analysis 58 are also presented in this section and summarized in Figure 3. The synthesized MCM‐41 nanoparticles had a specific surface area, pore volume and pore diameter of 1123.335 m 2 g −1 , 1.701 m 3 g −1 , and 2.342 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 2B, the percentage weight loss due to decomposition of the nanoparticles; MCM-41, MCM-N, MCM-B, and MCM-B-D were determined to be $15%, 20%, 27.5%, and 30%, respectively. These The results of the nitrogen sorption analysis 58 are also presented in this section and summarized in Figure 3. The synthesized MCM-41 nanoparticles had a specific surface area, pore volume and pore diameter of 1123.335 m 2 g À1 , 1.701 m 3 g À1 , and 2.342 nm, respectively.…”
Section: Physicochemical Properties Of the Silica Nanoparticlesmentioning
confidence: 89%
“…[ 45 ] The combination of hemostatic (Ca 2+ ) and antifibrinolytic (TXA‐NH 2 ) properties is efficient to stop hemorrhage. [ 46 ] These results indicated that all these factors contributed to the excellent pro‐coagulation performance of the J‐CMH@CaCO 3 /T.…”
Section: Resultsmentioning
confidence: 91%